Assessment Of Customer Satisfaction Of Samsung - Alsgayir, Mohamed Ibrahim Mohamed; , Dr. Anton Agus Setyawan, M.Si; , Drs. Ahmad Mardalis, MBA (2015)
The purpose of this study is to determine the customer satisfaction of using Samsung mobile phone. This research is quantitative, by taking samples of Samsung user especially of Samsung mobile phone. The study population is the entire subject of research is carried out by taking location in around of University Muhammadiyah of Surakarta, Semarang, Wonogiri and Surakarta. The technique of collecting data by using questionnaires. The data analysis technique is used Chi - Square test. The results are obtained showed that: There is difference perception between customer satisfaction to perceived usefulness.